Lingkungan mempengaruhi cara pandang seseorang - indi, rovida (Maliki Interdisciplinary Journal, 2025)
The environment is an external factor that significantly shapes a person’s worldview toward themselves, others, and social reality. This article aims to discuss the role of the environment in influencing individual perspectives through family, education, culture, and social interactions by reviewing studies conducted by lecturers of UIN Maulana Malik Ibrahim Malang and related literature. The method used is a literature review. The discussion shows that positive perceptions of the learning environment can increase motivation and academic achievement(Indriana & Novianto, 2020). Furthermore, UIN Malang’s Green Campus program demonstrates that physical and cultural campus environments foster critical, caring, and constructive perspectives. Thus, creating healthy academic, social, and cultural environments is essential in shaping students’ positive worldviews.